Effect of impeller speed on the Ni(II) ion flotation. Issue 3 (4th May 2019) - Sadat Hoseinian, Fatemeh; Rezai, Bahram; Kowsari, Elaheh; Safari, Mehdi
ABSTRACT: In this study, the effect of impeller speed on Ni(II) removal and water removal was evaluated in ion flotation. The results show that the Ni(II) removal increases with increasing impeller speed from 600 to 800 rpm from less than 41% to 88%, respectively, and after that, it decreases to 79% with increasing impeller speed to 900 rpm in the first 4 min of flotation. The water removal was increased with increasing impeller speed. The Ni(II) removal and water removal were modelled and described as the function of variables such as flotation time and impeller speed using the gene expression programming (GEP). The kinetics study also showed that the removal rate of Ni(II) ions and water were increased with increasing impeller speed.